PENGEMBANGAN DESAIN MEDIA PEMBELAJARAN SEJARAH BOOKLET BERBASIS SITUS MEGALITIK BATU BERAK LAMPUNG BARAT - M Ari Apriandi; Ragil Agustono (Swarnadwipa, 2018)
This development research aims to create a product based on Megalithic Site Stone Berak as an effort to overcome the limitation of cost, space and time by students which then function also to strengthen the understanding of local history of class X SMA 1 Sekincau.This research uses development research method adopted from R & D level 1 Sugiyono where in this research only validation test of product until the product reach feasibility based on validation test from material expert and media expert. In this research is intended to create a media based learning Site Megalithic Stone Berak, and products that will be produced by this research development method is a booklet based Site Megalithic Stone Berak material pre-period script.After making the product, the next step is the validation test. In the improvements made based on inputs and suggestions by validators on material validation at stage 1, a feasibility percentage of 77% is obtained. Then the media booklet validation by the material experts at stage 2, obtained the percentage of media booklet eligibility of 91.4%. And on the media validation at stage 1, obtained the percentage of eligibility of 82.4%. Then Validation media booklet by media experts in stage 2, obtained a percentage of eligibility of 89%.From these data, then in this case also been in harmony with the relevant theoretical study that the media booklet book-based Site Megalithic Stone Berak is said worthy trial and predicted that can be used as an innovative learning media in learning history, especially on learning local history.